2016
DOI: 10.1161/circoutcomes.116.002904
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Impact of Subsequent Depression in Patients With a New Diagnosis of Stable Angina

Abstract: Background-Depression is prevalent among patients with myocardial infarction and is associated with a worse prognosis.However, little is known about its importance in patients with chronic stable angina. We conducted a retrospective population-based cohort study to determine the occurrence and predictors of developing depression in patients with a new diagnosis of chronic stable angina. In addition, we sought to understand its impact on subsequent clinical outcomes. Methods and Results-Our cohort included pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Third, due to the high morbidity in the sample and the length of the follow-up period, our study suffered from a high drop-out rate. As the prognosis of patients with CAD and depression is poorer than that of patients with CAD that are not depressed [71,72,73], selection bias may have occurred, leading to an underestimation of the prevalence of depression and reducing the power of our study. Thus, we may have missed other depression loci in CAD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Third, due to the high morbidity in the sample and the length of the follow-up period, our study suffered from a high drop-out rate. As the prognosis of patients with CAD and depression is poorer than that of patients with CAD that are not depressed [71,72,73], selection bias may have occurred, leading to an underestimation of the prevalence of depression and reducing the power of our study. Thus, we may have missed other depression loci in CAD patients.…”
Section: Discussionmentioning
confidence: 99%
“…A study in >22 000 patients with a new diagnosis of stable angina observed that female sex was a predictor of developing depression after coronary angiography. Furthermore, in this cohort, the frequency of depressive symptoms was independently associated with a higher risk of death and admission for MI 29. Similarly, a study in 988 women referred for coronary angiography observed that women with a history of depression were hospitalized more often over 2.3 years of follow‐up than those without a history of depression.…”
Section: Discussionmentioning
confidence: 51%
“…A study by Thombs et al on patients with acute myocardial infarction (AMI) showed that survivors of AMI have constant depression [11]. Moreover, according to Kaptein et al, symptoms of depression after myocardial infarction are considered important risk factors of developing other cardiac conditions [12].…”
Section: Introductionmentioning
confidence: 99%